How does an animated video on human sense improving students’ with hearing impairment a concept understanding? - Shefa Dwijayanti Ramadani; Putri Nadila; Ferisa Prasetyaning Utami (Universitas Muhammadiyah Malang, 2024)
The quality of education for children with special needs must be continuously improved to help them fully develop their potential. However, students with hearing impairments often face challenges in comprehending complex scientific concepts due to limitations in vocabulary and the abstract nature of traditional teaching materials. This study focuses on the development of animated learning videos covering human sensory systems to enhance conceptual understanding among students with hearing impairments. The research employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) and a pre-experimental one-group pretest-posttest design to assess the effectiveness of the videos. The product was tested on 10th-grade students at Special Senior High School of Magelang. Validation results showed that the animated video met the media criteria for validity, while the content criteria achieved high validity with scores of 79.6% and 80.4%, respectively. The effectiveness of the animated videos was further supported by an N-Gain score of 0.78, indicating a high level of improvement in student understanding. These findings suggest that the developed animated videos are highly feasible and effective tools for improving the conceptual understanding of students with hearing impairments.